Conceptual framework of value creation through CSR in separate member of value creation chain - Jonikas Donatas (Bulletin of Geography. Socio-Economic Series)
The main goal of this paper is to prepare a conceptual framework which would help to determine where any kind of value might emerge while various actions of Corporate Social Responsibility (CSR) are implemented. Such conceptual framework is suggested as a backbone for further research and empiric justification in order to develop a simplified yet effective CSR outcome evaluation model which might be used in practice in any company. Such practical model should help to determine which CSR action might bring maximized value outcome with lowest costs. The main attention in this paper is concentrated only on a single company as a member of value creation chain (VCC). The paper lays foundation for perspective to develop the research in a holistic way - to evaluate the effect of CSR integration in whole VCC. Many authors have debated the different possibilities of simultaneously incorporating social, environmental and economic concerns into management thinking and practice (Aguilera et al., 2007) in organizational behavior; Buysse and Verbeke (2003); Starkey and Crane (2003); Barin-Cruz et al. (2006) in strategic management. All those scholars have been developing concept of CSR from different point of view. This paper concerns value creation through CSR as economical category. But therefore in order to indicate areas of possible value creation, various all above mentioned aspects of CSR concept are taken into account.